Is voting for young people? : with a postscript on citizen engagement - Wattenberg, Martin P., 1956- (New York : Pearson Longman, 2008)
This accessible, provocative, and brief book explores the reasons why the young are less and less likely to follow politics and vote in the United States, as well as in many other established democracies, and suggests ways of changing that.
The aging of regular newspaper readers -- The aging audience for politics on TV -- Don't ask anyone under 30 -- Where have all the young voters gone? -- Do young adults see voting as a civic duty? -- Does low youth turnout really matter? -- What can be done? -- Postscript : a new civic engagement among young people?
Includes bibliographical references and indexes.
Keywords: Young adults -- Political activity; Voting age; Political participation; Political culture